2019
DOI: 10.2174/1871530318666180801125258
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome, Thyroid Function and Autoimmunity - The PORMETS Study

Abstract: Background The prevalence of thyroid dysfunction and autoimmunity in the Portuguese population has not yet been estimated. However, the national prevalence of the metabolic syndrome remains high. The association of thyroid pathology with cardiovascular risk has been addressed but is still unclear. Our study aimed to evaluate the prevalence of thyroid dysfunction and autoimmunity and to assess the associations of thyroid-stimulating hormone and thyroid hormones and antibodies with metabolic syndrome, its compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
5
20
1
1
Order By: Relevance
“…In the present study, it was proved that fT4 was associated with components of MetS, which was validated in NHNES database and consistent with previous studies 21,22 . Therefore, the thyroid function screening should be also paid attention in MetS subjects.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was proved that fT4 was associated with components of MetS, which was validated in NHNES database and consistent with previous studies 21,22 . Therefore, the thyroid function screening should be also paid attention in MetS subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Another study on Portuguese population discovered a negative association of TPOAb positivity with MetS and its TG component. In contrast, no association of TgAb was not found with MetS or its components (20). Therefore, not only is there a lack of consistent findings in the relationship between thyroid autoantibody positivity and the prevalence of MAFLD, but also a lack of understanding of the respective roles of TPOAb and TgAb, which requires further study.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, studies have shown that the presence of thyroid antibodies are involved in glucose and lipid metabolic disorders ( 17 , 18 ). In addition, thyroid autoimmune may have a tumor-promoting role in breast cancer carcinogenesis ( 19 ) and may act as an independent CVD risk factor by promoting chronic inflammation ( 20 ). The relationship between thyroid antibodies and MAFLD remains unclear and few previous studies have been done.…”
Section: Introductionmentioning
confidence: 99%
“…Serum FT3 or total T3 were also evaluated in some studies. 15,16,22,27,33,3538,4547,49,54,57,60,73,74,7779,81,82,85,86,89,93,96,101,105110…”
Section: Studies Evaluating the Association Between Metabolic Syndrommentioning
confidence: 99%